2020
DOI: 10.1016/j.ijinfomgt.2019.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Land records on Blockchain for implementation of Land Titling in India

Abstract: This paper explores the usage of Blockchain Technology for land records management in India.The paper highlights issues like minimal transparency, accountability, incoherent data sets with different Government Departments pertaining to the same piece of land and delays in the current Land Records Management process and how these problems can be overcome using Blockchain Technology. The paper describes the current process of land records maintenance and land registration in the country. The paper also discusses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
74
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 172 publications
(101 citation statements)
references
References 8 publications
1
74
0
2
Order By: Relevance
“…Given the distributed way data is stored in Blockchain, applications related to logistics, land properties, electricity, government payments and smart contracts turn out to be appropriate, since the different actors involved in each process would benefit from the distributed ledger (Atzori, 2018;Buth, Wieczorek, & Verbong, 2019;Engin & Treleaven, 2019;Kossow, 2019;Li, Greenwood, & Kassem, 2019;Marchionni, 2018;Maza, 2019;Ølnes, Ubacht, & Janssen, 2017;Thakur, Doja, Dwivedi, Ahmad, & Khadanga, 2019). Polls, Supply Chain, Digital Identity and Building Construction share Blockchain's data processing efficiency; the technology stands out for its security in storing data, as they are important information, be it for social control -elections and document maintenance -or for the control of buildings and food and/or medication, and the public administration must control or regulate these processes (Abelseth, 2018;Johnson, 2019;Kossow, 2019;Lander & Cooper, 2017;Li et al, 2019;Tseng, Liao, Chong, & Liao, 2018).…”
Section: Rsl Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the distributed way data is stored in Blockchain, applications related to logistics, land properties, electricity, government payments and smart contracts turn out to be appropriate, since the different actors involved in each process would benefit from the distributed ledger (Atzori, 2018;Buth, Wieczorek, & Verbong, 2019;Engin & Treleaven, 2019;Kossow, 2019;Li, Greenwood, & Kassem, 2019;Marchionni, 2018;Maza, 2019;Ølnes, Ubacht, & Janssen, 2017;Thakur, Doja, Dwivedi, Ahmad, & Khadanga, 2019). Polls, Supply Chain, Digital Identity and Building Construction share Blockchain's data processing efficiency; the technology stands out for its security in storing data, as they are important information, be it for social control -elections and document maintenance -or for the control of buildings and food and/or medication, and the public administration must control or regulate these processes (Abelseth, 2018;Johnson, 2019;Kossow, 2019;Lander & Cooper, 2017;Li et al, 2019;Tseng, Liao, Chong, & Liao, 2018).…”
Section: Rsl Resultsmentioning
confidence: 99%
“…From this, it is concluded that Blockchain could be a tool capable of working for the benefit of society, bringing information security and ensuring compliance with the legislation, through the encrypted government data storage model and distributed ledgers. According to the analysis presented in section 3.2, it appears that Blockchain is a tensioned model for the storage of data dealing with land ownership and its demarcation, allowing the facilitation of the process of purchase and registration of real estate and/or land, as well as more transparency (Maza, 2019;Thakur et al, 2019). Land ownership or land demarcation disputes, whether agrarian, quilombola, indigenous or urban and not yet implemented in land reform (Reis, 2012), could be simplified by using the Blockchain to define land tenure and immutability, reducing conflicts.…”
Section: Blockchain Applications and Potential Consequencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Vinay Thakur et al [43], explored the need for blockchain technology for safekeeping of land records in India. Authors also illustrated their work as a system, build using blockchain technology for implementing tamper-proof and authentic rights of ownership for land titling in India.…”
Section: Comparison With a Similar Systemmentioning
confidence: 99%
“…A detailed discussion and comparison of the work proposed by Vinay Thakur et al and by us detailed in the forthcoming paragraph, the difference between the two is former uses blockchain technology for land titling, while later uses for land registration. Besides, the paper [43] explains the only theoretical concept and lacks in experimental proofs.…”
Section: Comparison With a Similar Systemmentioning
confidence: 99%